A Teaching-Learning Sequence applied in Science classes: A model based on problematizing microplastics (Research, Society and Development, 2025)
Plastic pollution and an increase in the presence of microplastics in several environments are serious and current problems. However, they are approached at school in a way that is decontextualized and disconnected from the reality of students. Having that in mind, this paper aimed to verify the relevance of a Teaching-Learning Sequence centered around microplastics, within the subject of food webs, an ecology theme taught during Science classes. We evaluated the benefits of the different teaching strategies chosen to form the sequence that had as main target students of a private school from Campos dos Goytacazes/RJ. Such evaluation was made by the implementation of questionnaires before, during and after each phase of the sequence. Our findings have shown that, initially, students did not know much about microplastics and their negative impacts on the environment, even though they were aware of the constant presence of plastic in their daily lives. Our findings also elucidate that students were able to gain environmental consciousness as the sequence advanced. Considering our results, we suggest an advantage to the teaching-learning process when previously defined subjects are approached with a theme that is present in students' daily lives, increasing knowledge gain in both fronts. Therefore, we highlight the importance of continuing to implement such strategies when teaching Science classes.